NEUTROPHIL INFILTRATION BASED ON CLINICOHISTOPATHOLOGICAL CHARACTERISTICS IN SEROUS OVARIAN CARCINOMA - Fertilita, Soilia; Aisyah Mulya Zhafirah; Wresnindyatsih; Veny Larasati; Riana Sari Puspita Rasyid (Majalah Kedokteran Sriwijaya, 2024)
Ovarian cancer is the main cause of death globally and is the third most common cancer in women in Indonesia. Neutrophils play a role in response against cancer and are related to the patient’s prognosis. The aim of this study was to determine differences in neutrophil infiltration based on the clinicohistopathological characteristics of serous ovarian carcinoma tissue at RSUP Dr. Mohammad Hoesin Palembang. This research used a cross-sectional method. The samples used were archived serous ovarian carcinoma tissue preparations with Hematoxylin-Eosin staining from the Anatomical Pathology Department and clinical data from the Medical Records Installation of RSUP. Dr. Mohammad Hoesin Palembang. Observations were made by identifying neutrophil cells that infiltrate the microtumor environment in the stromal and intratumoral areas. Data were obtained from 35 patients diagnosed with serous ovarian carcinoma. Most of the samples were aged 40-60 years (48.6%) with the most histological subtype (74.3%) being HGSC and 77.1% were at an advanced stage. There were no significant differences between neutrophil cell infiltration based on clinicohistopathological characteristics, including age (stromal p=0.85 and intratumoral p=0.22), subtype (stromal p=0.29 and intratumoral p=0.72), and FIGO stage (stromal p=0.35 and intratumoral p=0.38). It can be concluded that neutrophil infiltration does not differ based on clinicohistopathological (age, subtype, and stage) characteristics in serous ovarian cancer.